MANAJEMEN NYERI BAYI PREMATUR: ANALISIS PENGETAHUAN DAN SIKAP PERAWAT NICU - Reisy Tane; Ikhsanuddin Ahmad Harahap; Farida Linda Sari Siregar; Azwar Azwar (Jurnal Keperawatan Widya Gantari Indonesia, 2026)
Pain in premature infants is often not optimally managed in the Neonatal Intensive Care Unit (NICU). Nurses play a central role in pain assessment and management, making their knowledge and attitudes crucial factors in the success of neonatal pain management. This study aimed to analyze the knowledge and attitudes of NICU nurses regarding pain management in premature infants. The study used a quantitative descriptive design with a cross-sectional approach. A sample of 22 NICU nurses was selected through total sampling from several hospitals in Medan City. Data were collected using a knowledge and attitude questionnaire regarding pain management in premature infants, then analyzed descriptively using frequency distributions and percentages. The study found that most respondents had nursing education and were in the adult age group. The majority of nurses' knowledge level was in the sufficient category, with the lowest scores being on the use of pain assessment scales and non-pharmacological interventions. Nurses' attitudes were generally positive, indicating good support for the importance of pain management in premature infants. NICU nurses already have positive attitudes toward pain management, but their knowledge still needs to be improved to ensure more evidence-based practice. Structured training, the implementation of standardized pain scales, and regular evaluation are needed to improve the quality of neonatal nursing care.